1999
DOI: 10.1295/polymj.31.51
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions of Dimeric Liquid Crystals Containing Long Odd-Numbered Methylene Spacers

Abstract: ABSTRACT:A series of o:,w-bis{4-(4-biphenyloxycarbonyl)phenyl} alkanedioates (BPA-n) dimeric liquid crystals having long odd-numbered methylene spacers was prepared. The number of methylene groups in the flexible alkyl spacer has been varied from 9 to 21. Long period L of crystalline BPA-n obtained by X-ray powder diffraction were shown as a linear equation of the number n of methylene units, as follows, L= l.I6n + 35.2 (A). BPA-21 showed no liquid crystalline phase. BPA-19 is monotropic nematic. The other BPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Among all the compounds, 7c exhibited a mesophase at RT on cooling which could be due to the bulky chloro groups which prevent packing into the crystalline phase. Compounds 6 exhibited lower isotropization temperatures as compared to 7 on heating which could be explained based on odd–even alkyl spacer effects as also observed earlier . Moreover, it was found that on increasing the size of functional group in ortho substitution, the clearing temperatures from crystal to LC as well as isotropization temperatures decreased.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Among all the compounds, 7c exhibited a mesophase at RT on cooling which could be due to the bulky chloro groups which prevent packing into the crystalline phase. Compounds 6 exhibited lower isotropization temperatures as compared to 7 on heating which could be explained based on odd–even alkyl spacer effects as also observed earlier . Moreover, it was found that on increasing the size of functional group in ortho substitution, the clearing temperatures from crystal to LC as well as isotropization temperatures decreased.…”
supporting
confidence: 70%
“…Compounds 6 exhibited lower isotropization temperatures as compared to 7 on heating which could be explained based on odd−even alkyl spacer effects as also observed earlier. 22 Moreover, it was found that on increasing the size of functional group in ortho substitution, the clearing temperatures from crystal to LC as well as isotropization temperatures decreased. The similar effect was also observed on cooling from the isotropic states.…”
mentioning
confidence: 99%
“…There is a clear dependence of the ΔS on the composition of the molecules constituting liquid crystals. For example each methyl or methylene unit (here contained in the four propyl chains in TePrA + cation) contributes around 18 and 7 Jmol -1 K -1 , respectively, to the overall ΔS in the phase change from crystal at RT to isotropic liquid at HT 18 , 19 . Therefore, we might suspect that a similar transition takes place at HT in the title crystal, resulting in extremely disordered crystal resembling a quasi-isotropic liquid.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Aromatic main-chain thermotropic liquid crystalline polyesters (TLCPs) have been extensively investigated owing to their versatile nano-orientation and excellent functionality that are derived from their nanostructures. They are used as (super)­engineering plastics with high thermal stability, chemical resistance, and dimensional stability; low gas permeability; and excellent mechanical properties. However, wholly aromatic TLCPs often undergo thermal degradation prior to isotropization . Various aromatic polyesters have been developed to overcome this problem through copolymerization and the use of semiflexible TLCPs, in which flexible spacers are incorporated into the main chain.…”
Section: Introductionmentioning
confidence: 99%